DEVELOPMENT MARKETING STRATEGY FOR RAMADA ENCORE KIEV (Economics and region, 2017)
UDC 339.138:640.41 Koryuhina Catherine, Mg.oec., Mg.Phil. Assist.Prof. Oleksij Sorokin. ISMA University. Latvia. Developing Marketing Strategy for Ramada Encore Kiev. The article gives the analysis of marketing strategy of Ramada Encore Kiev Hotel, highlights the importance of marketing concept, and marketing strategy, and formulates the ways of improving the situation with the help of marketing activities.The hospitality marketing mix model is used as the theoretical basis. Besides, financial reports, international organisations statistics, SWOT analysis, PESTEL analysis and other methods are used. Nowadays hospitality is fast growing and developing industry. The aim of this work is to find suitable new advertising strategies that can make for hotel’s development. Keywords: marketing strategy, concept, improving, hospitality, theoretical issues, statistics, suggestions.